A widow, a victim, a mother. Issue 2 (July 2015) - Verma, Shweta
<x xml:space="preserve">Abstract</x> Using a case study, this paper describes initial results from qualitative research with women widowed as a result of conflict in Kashmir. Recognising resilience as a process that contributes to a sense of wellbeing, this paper highlights how this process also often involves experiencing and exercising overlapping identities of being a 'victim', 'widow, and a 'mother' for women within conflict contexts. Further, the paper questions simplistic readings of resilience and wellbeing that classify people as resilient or not resilient, and classify relationships, identities, and feelings in terms of 'good' or 'bad' by reflecting on questions such as: 'is belief or portrayal of oneself as a victim unhelpful or negative? Or, is worrying bad?' The case study included here is one of the fifty qualitative interviews conducted as part of PhD research on resilience among women widowed due to conflict in Kashmir.